Religion and violence: a dialectical engagement through the insights of Bernard Lonergan - Arcamone, Dominic (James Clarke & Co, 2016)
The aim of Religion and Violence is to engage dialectically key symbols of religiously motivated violence through the insights of Bernard Lonergan. Sociologists and psychologists argue the link between religion and violence. Religion is viewed more as part of the problem and not part of the solution to violence. Bernard Lonergan’s insights have helped the author arrive at a number of conclusions regarding the link between religion and violence. He argues that there is a difference between distorted religion and genuine religion, between authenticity and inauthenticity of the subject. Distorted religion has the capacity to shape traditions in ways that justify violence, while genuine religion heals persons, helps them make different moral decisions when confronted with situations of conflict, and aims to explore new ways of understanding themselves as shaping history toward progress. Further, Religion and Violence, while arguing from within the Catholic Christian tradition, nevertheless seeks to provide a number of categories that will speak to people from other cultural traditions. Since many of the examples of religious violence cited by commentators come out of the Islamic tradition, the author has evidenced and explored more authentic aspects of the Islamic tradition that would help provide a solution to violence